2018
DOI: 10.1007/s12035-018-1240-4
|View full text |Cite
|
Sign up to set email alerts
|

CD73 Downregulation Decreases In Vitro and In Vivo Glioblastoma Growth

Abstract: Glioblastoma is the worst and most common primary brain tumor. Here, we demonstrated the role of CD73, an enzyme responsible for adenosine (ADO) production, in glioblastoma progression. ADO increased glioma cell viability via A1 receptor sensitization. CD73 downregulation decreased glioma cell migration and invasion by reducing metalloproteinase-2 and vimentin expression and reduced cell proliferation by 40%, which was related to necrosis and sub-G1 phase blockage of cell cycle. Those effects also involved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 66 publications
8
68
2
Order By: Relevance
“…The variation of gene expression not completely reflect the profile of GMT protein expression demonstrating that, even though ADO could induce some traits of the mesenchymal phenotype, it is not able to trigger a complete transition. These results are in accordance with the ability of ADO to promote the Vimentin gene expression in C6 rat glioma cells [ 76 ] and strengthen the pivotal role exerted by extracellular ADO in the control of glioma aggressive traits in human cells. Interestingly, ADO regulates the induction of GMT in U343MG almost in part through the increase of ERK1/2 phosphorylation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The variation of gene expression not completely reflect the profile of GMT protein expression demonstrating that, even though ADO could induce some traits of the mesenchymal phenotype, it is not able to trigger a complete transition. These results are in accordance with the ability of ADO to promote the Vimentin gene expression in C6 rat glioma cells [ 76 ] and strengthen the pivotal role exerted by extracellular ADO in the control of glioma aggressive traits in human cells. Interestingly, ADO regulates the induction of GMT in U343MG almost in part through the increase of ERK1/2 phosphorylation.…”
Section: Discussionsupporting
confidence: 84%
“…Herein, we demonstrate that the prolonged exposure to a high ADO concentration (100 µM) promotes the glioma motility in vitro. This result is in accordance with the ability of CD73 to enhance cell adhesion through ADO production, thereby promoting cell migration and invasion in different cancer cells and in glioma cells [ 29 , 38 , 76 , 82 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…242 , 291 Part of the evidence to support the role of CD39 and CD73 in tumorigenesis and inflammation is that mice deficient in CD73 or CD39 are susceptible to autoimmunity/inflammation and be tumor resistant as a result of ADO-mediated immunosuppression alleviation. 292 294 …”
Section: Study and Progress Of Adenosine In The Nk Cell Cancer Immunomentioning
confidence: 99%
“…Through mass cytometry and scRNA-seq, in GMB a unique subset of macrophages expressing high levels of CD73 able to persist after anti-PD-1 therapy was observed (88). Notably, a number of reports have shown that CD73 can induce immunosuppression in GMB (157,158).…”
Section: Other Cells Than T Lymphocytesmentioning
confidence: 99%